The Effect of Entrepreneurship Achievement and Family Economic on Entrepreneurship Interest of XII Automotive Grade Students SMK Taman Karya Madya Jetis Yogyakarta Year 2013/2014 - Tri Kurniawan Krisbowo (Universitas Sarjanawiyata Tamansiswa, 2014)
The objective of this research was to observe an effect of Entrepreneurship Achievement and Family Economic on Entrepreneurship Interest of XII Automotive Grade Students SMK Taman Karya Madya Jetis Yogyakarta Year 2013/2014. While the hypotheses were (1) there was a positive effect of entrepreneurship achievement to the interest of entrepreneurship; (2) there was a positive effect of family economic to the interest of entrepreneurship; and (3) entrepreneurship achievement and family economic give a positive effect to entrepreneurship interest of XII Automotive Grade Students SMK Taman Karya Madya Jetis Yogyakarta Year 2013/2014. This research included to ex-post facto research. The populations, which was the research sample, were 84 students of XII Grade Automotive Mechanical Engineering Program of SMK Taman Karya Madya Jetis Yogyakarta Year 2013/2014. The methods of data collection were questionnaire and documentation. Descriptive analysis was used to analyze the data. Partial correlation was used at first and second hypothesis test, while two multiple regression predictors was used at third hypothesis test that preceded with test requirements, which were test of normality, linearity and intercorrelations. The results showed that (1) entrepreneurship achievement give a positive and significant effect to the interest of entrepreneurship; (2) family economic give a positive and significant effect to the interest of entrepreneurship; and (3) entrepreneurship achievement and family economic give a positive and significant effect to entrepreneurship interest. These results indicated that entrepreneurship achievement and family economic effected the determining of entrepreneurship interest.